2015
DOI: 10.1155/2015/148954
|View full text |Cite
|
Sign up to set email alerts
|

Cementation of Glass-Ceramic Posterior Restorations: A Systematic Review

Abstract: Aim. The aim of this comprehensive review is to systematically organize the current knowledge regarding the cementation of glass-ceramic materials and restorations, with an additional focus on the benefits of Immediate Dentin Sealing (IDS). Materials and Methods. An extensive literature search concerning the cementation of single-unit glass-ceramic posterior restorations was conducted in the databases of MEDLINE (Pubmed), CENTRAL (Cochrane Central Register of Controlled Trials), and EMBASE. To be considered fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 80 publications
2
34
0
Order By: Relevance
“…Thermal cycling regime is considered the most widely-used procedure to simulate the physiological aging experienced by biomaterials in the dental practice. Consequently, it is routinely employed in experimental studies to evaluate material's performance [25]. In this study, teeth were subjected to 1000 cycles from 5 to 55oC to simulate the oral hot and cold conditions with dwell tie 20 seconds and 7 seconds transfer time [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal cycling regime is considered the most widely-used procedure to simulate the physiological aging experienced by biomaterials in the dental practice. Consequently, it is routinely employed in experimental studies to evaluate material's performance [25]. In this study, teeth were subjected to 1000 cycles from 5 to 55oC to simulate the oral hot and cold conditions with dwell tie 20 seconds and 7 seconds transfer time [42].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional glass ionomer has been introduced into the dental field as a hybrid material of silicate cements and polycarboxylate cements to make the best out of the two materials: fluoride release to prevent caries [22] (silicate cement) and adhesion to dental substrates (polycarboxylate cement) [23]. Several studies [7,19,[24][25][26] suggested that, due to its chemical adhesion to tooth structure and good biocompatibility as a conventional cement, glass ionomer can be used for cementation of full coverage zirconia restorations.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…It is known that the long-term success rate of these materials is influenced by various factors. The most influential of these for effective adhesive restorations include the adhesive procedures, the quality of the remaining tooth and the type of material used [8]. This has led to a growing interest in the study of ceramic materials and their related aspects.…”
Section: Introductionmentioning
confidence: 99%
“…26 With respect to the technique itself, adhesive cementation can be considered more difficult as it is more time-consuming and requires improved moisture control in comparison with water-based cementation. 1 Posterior crowns exhibit higher fracture rates than anterior crowns, and indirectly bonded restorations in molars exhibit higher failure rates than those in premolar crowns. 27 The clinical success and reliability of the ceramic systems are directly related to the mechanical integrity of their constituent materials and bond strength at the ceramicadhesive interface.…”
mentioning
confidence: 99%
“…To satisfy the esthetic and functional requirements in restorative dentistry, cements, cementation techniques, bonding systems, and bonded glass-ceramics have been developed and have become popular. 1 To ensure adequate resistance and esthetics, a product is needed between the tooth and the ceramic restoration. 2 Cements are necessary to provide good marginal adaptation and for ensuring the retention of the restoration.…”
mentioning
confidence: 99%